CONTRIBUTION OF FINANCIAL DISTRESS INDICATORS TO CORPORATE FAILURE AMONG COMMERCIAL BANKS IN KENYA - WEKULLO KUCHIO, LEONARD JACOB (Kabarak University, 2012)
This study examines the contribution of financial distress indicators to corporate failure for commercial banks in Kenya. Specifically, the study examined the contribution of cash flows, liquidity, solvency, profitability and efficiency, utilization of shareholders’ funds and non performing loans to corporate failure. Other researchers’ work was reviewed critically. Quantitative research design was employed and the probit regression model estimated to enable the researcher predict the probability that corporate failure occurs given that any of the financial distress indicators occurs. Data collection was through retrieval from secondary sources and covered a population of all 47 banks that were in operation and the ones that collapsed during the study period. The data was then analyzed using panel data probit regression method. Findings from the study indicate that a reduction in Profitability and efficiency (P and E) and Cash flow will lead to probability of corporate failure while an increase in Non Performing Loans (NPL) and Solvency will lead to probability of corporate failure
Keywords: Corporate failure; Financial distress indicators; Commercial Banks; Panel data; Probit regression method